2006
DOI: 10.1007/s00484-006-0065-4
|View full text |Cite
|
Sign up to set email alerts
|

Statistical modeling of valley fever data in Kern County, California

Abstract: Coccidioidomycosis (valley fever) is a fungal infection found in the southwestern US, northern Mexico, and some places in Central and South America. The fungus that causes it (Coccidioides immitis) is normally soildwelling but, if disturbed, becomes air-borne and infects the host when its spores are inhaled. It is thus natural to surmise that weather conditions that foster the growth and dispersal of the fungus must have an effect on the number of cases in the endemic areas. We present here an attempt at the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…Studies to date have demonstrated a strong incidence–climate connection in Arizona, 15 but not in California 17 . Perhaps this is because the latter studies use wind and not PM 10 as a proxy for spore abundance in the atmosphere.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies to date have demonstrated a strong incidence–climate connection in Arizona, 15 but not in California 17 . Perhaps this is because the latter studies use wind and not PM 10 as a proxy for spore abundance in the atmosphere.…”
Section: Discussionmentioning
confidence: 99%
“…We used 9 years (Jan 1995–Dec 2003) of weekly mean atmospheric conditions and incidence data to construct a statistical model which allows a degree of prediction 17 . We presented a generalized autoregressive moving average (GARMA) model that maximizes the accuracy of prediction while minimizing the number of input variables 19 .…”
Section: Kern County: Incidence–weather Correlations and Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…In studies performed in Kern County, California, precipitation 8 to 20 months prior played only a small role in incidence of coccidioidomycosis in that area [29]. In a follow-up study, Talamantes et al [30] found that recent increases in the incidence rate of coccidioidomycosis in Kern County were more likely related to host factors than to environmental factors. Currently, California [31] and Arizona [25] are experiencing drought conditions.…”
Section: Environmental Factorsmentioning
confidence: 96%